Consideration of pelvic floor myofascial release for overactive bladder. Issue 2 (April 2020) - Wolff, Birte J.; Joyce, Cara J.; McAlarnen, Lindsey A.; Brincat, Cynthia A.; Mueller, Elizabeth R.; Fitzgerald, Colleen M.
Abstract: Introduction: Physical therapy has been shown to be effective for women with overactive bladder (OAB). We report on our experience with pelvic floor physical therapy (PFPT) with or without myofascial release as treatment for women with symptoms of urinary urgency or urge incontinence. Methods: We performed a retrospective chart review, of patients who presented to our tertiary care Urogynecology practice. These women were evaluated and treated between August 2016 and December 2016. We abstracted for symptoms as per history of present illness and the pelvic floor muscle examination. PFPT progress notes were reviewed to determine whether patients received myofascial release techniques, or if therapy was limited to behavioral interventions and urge suppression techniques. We recorded the number of PFPT sessions attended, and whether the patient reported improvement. Results: 77 patients with symptoms of OAB met inclusion criteria and initiated PFPT. Myofascial tenderness of the pelvic floor muscles was found in 56.5% of patients. PFPT was limited to behavioral and urge suppression in 18 patients, while 59 patients received myofascial release techniques. Improvement was reported by 71.4% (n = 55/77) of patients. Improvement increased with number of sessions attended: 1–2: 6% (1/17), 3–5: 94% (16/17), 6–8: 91% (29/32), and >8: 80% (9/11) improved, respectively (p < 0.001). Among patients who had myofascial release, 84.7% reported improvement when compared to only 27.8% of patients without myofascial release. Conclusions: The data support the inclusion of myofascial release during pelvic floor physical therapy for overactive bladder. At least three sessions of PFPT are necessary for patient reported improvement.